Adherence to Overactive Bladder Syndrome Treatments Recent Developments and Future Perspectives - Robinson D; O'Kane M; Cardozo L (International Journal of Women's Health, 2023)
Dudley Robinson, Miriam O’Kane, Linda Cardozo Department of Urogynaecology, King’s College Hospital, London, UKCorrespondence: Dudley Robinson, Department of Urogynaecology, King’s College Hospital, Suite 8, Level 3, Golden Jubilee Wing, London, SE5 9RS, UK, Tel +447966485503, Email dudley.robinson@nhs.netAbstract: Overactive bladder (OAB) is a common and distressing condition which is known to have a significant effect on Health-Related Quality of Life (HRQoL). Whilst all patients complaining of overactive bladder symptoms will, in theory, initially benefit from conservative measures, many will require pharmacological therapy. Antimuscarinics currently remain the most commonly used drugs to treat OAB although compliance and persistence can be poor due to concerns regarding adverse events and lack of efficacy. This review will explore the common management strategies for OAB with a particular focus on patient adherence to therapy including compliance and persistence. The role of antimuscarinics and the B3-agonist, mirabegron, will be considered along with barriers to their efficacy and adoption. For those patients in whom conservative and pharmacological treatment proves ineffective or is unsuitable, the management of refractory OAB will also be considered. In addition, the role of current and future developments will be examined.Keywords: OAB, adherence, compliance, persistence, antimuscarinics, β3 agonists